The Analysis of High Order Thinking Skills in the TPS Cooperative Learning Model for Narrative Text Materials in Class XI at SMA Darul Mustofa Bangkalan - Dwi Ratna Ningsih; Sulis Janu Hartat; Sri Yuni Hanifah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
In this study, there are several problem formulations, namely is there an effect of the TPS cooperative learning model for narrative text material at Darul Mustofa High School Bangkalan and is there an effect of high order thinking skills on the TPS cooperative learning model for narrative text material at Darul Mustofa High School Bangkalan. With the aim of the study to determine the effect of the TPS cooperative learning model for narrative text material at Darul Mustofa High School Bangkalan and to determine whether there is an effect of high order thinking skills on the TPS cooperative learning model for narrative text material at Darul Mustofa High School. This study uses a quantitative approach in which the type of experimental research is a quasi-experimental design in the form of a time series design. The advantages of this design are that it only uses one group so that it does not require a control group, so that the discussion is more detailed and focused to get the research objectives. With the pre-test before the treatment is carried out and the post-test after the treatment is carried out, the pre-test and post-test have the same types of items and have been validated. The TPS cooperative learning model on the dependent variable, namely learning outcomes called the determinant coefficient (R Square) obtained a value of 0.271, meaning that the influence of the variable, namely the TPS cooperative learning model, has a percentage of 27.1%, the effect of HOTS and TPS cooperative learning model on student learning outcomes obtained 0.233 or 23.3% affect